A method for degrading polyethylene terephthalate
PET is degraded through the thermoelectric coupling method, which solves the problems of low PET recycling and utilization rate and environmental pollution, and achieves efficient degradation and full recycling of PET, and generates high value-added products.
Patent Information
- Application Number
- CN202211713503.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing PET recycling technology has problems such as low recycling rates, insufficient utilization of recycled substances and the generation of secondary solid waste. It is urgently needed to have a sustainable and efficient PET waste treatment method.
Polyethylene terephthalate was degraded by thermoelectric coupling method. By mixing potassium hydroxide, PET and sodium hydroxide in a crucible, heating in a reactor and applying voltage and current, gas and liquid phase products were collected, and the solid phase products were finally collected.
This method can efficiently degrade PET, save energy, improve environmental pollution problems, and generate high value-added gas and liquid phase products, as well as useful pore amorphous carbon products, so that PET can be recycled and utilized.
Smart Images

Figure CN116199219B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste plastic degradation, in particular to a method for degrading polyethylene terephthalate. Background Art
[0002] Polyethylene terephthalate (PET) is a polyester plastic and the most commonly used material for producing our common beverage bottles. It is a condensation product of terephthalic acid and ethylene glycol, and belongs to thermoplastic polyester and saturated polyester. In 2020, the PET production capacity was about 110.17 million tons, and the output was about 79.92 million tons. About 67% was used for polyester production, about 5% was used for various polyester bottles, and 5% was used for film production. PET bottles have great recycling necessity and value. In 2017, Japan's PET bottle recycling rate was as high as 92%.
[0003] At present, the development of PET still maintains a strong momentum. With the rapid development of the PET industry, although PET does not cause direct harm to the environment, due to the huge amount of waste after its use and its strong resistance to the atmosphere and microbial agents, the existing recycling technology still has problems such as low recovery rate, insufficient utilization of recycled materials, and generation of secondary solid waste (i.e., solid residue). Therefore, there is an urgent need for a sustainable and efficient PET waste treatment method to solve the above problems caused by PET waste.
[0004] In view of the typical structural characteristics of PET and its increasing waste generation trend, the present invention aims to provide a method capable of fully recycling PET waste. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for degrading polyethylene terephthalate, which comprises the following steps:
[0006] (1) Put potassium hydroxide, polyethylene terephthalate, and sodium hydroxide into a crucible and mix them evenly;
[0007] (2) inserting two electrodes, serving as a cathode and an anode, into a crucible, fixing the crucible in a reactor, sealing the reactor and heating it, and after the temperature of the reactor stabilizes at a first preset temperature, applying a preset voltage and a preset current to the reactor for degradation, and collecting gaseous products and liquid products;
[0008] (3) lowering the temperature of the reactor to a second preset temperature, and then cooling to room temperature;
[0009] (4) Collect the solid phase products in the reactor.
[0010] The above technical solution of the present invention has the following advantages:
[0011] The thermoelectric coupling method provided by the present invention can save energy, improve environmental pollution problems, and efficiently generate hydrogen and light hydrocarbon fuels for PET degradation. Compared with the traditional single pyrolysis method, the conversion rate of PET degradation is higher, not only high value-added gas phase products and liquid phase products are obtained, but also porous amorphous carbon products with utilization value are obtained, so that PET can be more fully recycled and no solid waste is discharged into the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The TG curve and DSC curve of PET are shown.
[0013] Figure 2 The PET thermally assisted cyclic voltammetry curves (30 mV / s, -1.5 V to 1.5 V, 400° C., 420° C.) are shown.
[0014] Figure 3 Shown is the effect of current intensity on the PET degradation efficiency (400°C).
[0015] Figure 4 The effect of temperature on the polyester degradation efficiency in a single pyrolysis process is shown.
[0016] Figure 5 The effect of temperature on the degradation of PET by thermoelectric coupling is shown.
[0017] Figure 6 The effect of reaction time on the degradation of PET by a single pyrolysis process (0.5 g, 400 °C) is shown.
[0018] Figure 7 The effect of reaction time on the degradation effect of thermoelectrically coupled PET is shown (0.5 g, 1.5 V, 400 °C).
[0019] Figure 8 A SEM image (440°C, 0V) of a single pyrolysis PET solid product is shown, wherein Figure a, Figure b, and Figure c are at magnifications of 50.00KX, 20.00KX, and 10.00KX, respectively.
[0020] Fig. 9 The SEM images of the solid product of thermoelectrically coupled degradation of PET are shown (440°C, 1.5V), wherein Figure a, Figure b and Figure c are at magnifications of 10.00KX, 5.00KX and 2.00KX, respectively.
[0021] Fig.10 The XRD curve of the solid product of thermoelectric coupled degradation is shown (440℃, 1.5V).
[0022] Fig.11 A single pyrolysis solid product XRD curve (440° C., 0 V) is shown.
[0023] Fig.12 Shows the gas phase composition and content of polyester plastic degradation (0.5g PET, 440℃, 120min).
[0024] Fig.13 It is a schematic diagram of the device for degrading polyethylene terephthalate used in Example 1 of the present invention; the accompanying drawings are marked as follows: 1, power supply, 2, electric heating furnace, 3, reaction container, 4, thermocouple, 5, water bath device, 6, U-shaped tube, 7, drying tube, 8, pump, 9, air bag, 10, temperature control box. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The present invention provides a method for degrading polyethylene terephthalate, which comprises the following steps:
[0027] (1) Put potassium hydroxide, polyethylene terephthalate, and sodium hydroxide into a crucible and mix them evenly;
[0028] (2) inserting two electrodes, serving as a cathode and an anode, into a crucible, fixing the crucible in a reactor, sealing the reactor and heating it, and after the temperature of the reactor stabilizes at a first preset temperature, applying a preset voltage and a preset current to the reactor for degradation, and collecting gaseous products and liquid products;
[0029] (3) lowering the temperature of the reactor to a second preset temperature, and then cooling to room temperature;
[0030] (4) Collect the solid phase products in the reactor.
[0031] According to some preferred embodiments, in step (2), the electrode is a spiral electrode; more preferably, the spiral electrode is made of nickel wire. Further preferably, the diameter of the spiral electrode is 1.8 cm to 1.2 cm (for example, 1 cm).
[0032] According to some preferred embodiments, the diameter d of the nickel wire is 0.5 mm to 1 mm, the total winding length l of the nickel wire is 20 cm to 30 cm, and the number of windings is 10 to 20.
[0033] According to some preferred embodiments, in step (1), the polyethylene terephthalate is dried at 90° C. to 110° C. (eg, 100° C.) for 4 min to 6 min (eg, 5 min) before being placed in the crucible.
[0034] According to some preferred embodiments, the crucible is a corundum crucible; more preferably, the size of the crucible is diameter×height=40 mm×80 mm; further preferably, the crucible is pre-dried before use.
[0035] According to some preferred embodiments, in step (1), the mass ratio of KOH, PET and NaOH is (4-6):1:(3-5) (for example, 5.6:1:4). The KOH / NaOH mixed alkali system acts as an electrolyte during the reaction, that is, a current is formed between the cathode and anode through the mixing of PET and the mixed alkali.
[0036] According to some preferred embodiments, in step (2), the distance between the two electrodes is 0.8 cm to 1.2 cm (eg, 1.0 cm).
[0037] According to some preferred embodiments, in step (2), the heating rate is 9°C / min to 10°C / min, and the first preset temperature is 400°C to 440°C (e.g., 410, 420 or 430°C); and most of the organic products generated by the reaction exist in a gaseous state at 400°C to 440°C.
[0038] According to some preferred embodiments, the preset voltage is 1.4 to 1.6 V (eg, 1.5 V), and the preset current is 0.1 A to 0.4 A (eg, 0.2 or 0.3 A).
[0039] According to some preferred embodiments, the preset time is 60 min to 300 min (eg 100 or 200 min).
[0040] According to some preferred embodiments, in step (2), the first preset temperature is 440°C, the preset voltage is 1.5V, the preset time is 120min, and preferably, the preset current is 0.4A.
[0041] According to some preferred embodiments, in step (3), the gaseous products are collected in the following manner: argon gas is introduced into the reactor, and the gaseous products in the reactor are collected into an air bag by using the Ar exhaust method. After the degradation reaction is completed, the gaseous products can pass through a condensing device (a U-shaped tube cooled by a water bath) and a drying device (a drying tube filled with color-changing silica gel) in sequence under the action of an air sampling pump. The liquid products are condensed on the inner wall of the U-shaped tube, and the gaseous products are collected in an air bag after being dried. The gaseous products are dried considering that the presence of water vapor may cause certain damage to the gas chromatograph.
[0042] According to some preferred embodiments, in step (3), the second preset temperature is 150-250° C. (eg, 200° C.).
[0043] According to some preferred embodiments, in step (4),
[0044] The solid product is obtained by the following method: after the degradation is completed, the solid phase product in the reactor is dissolved in water, neutralized with hydrochloric acid to pH = 2.5 to 3.5 (for example, pH = 3), a solid suspension is obtained, filtered, the obtained solid is rinsed with acetone, and then dried. The solid phase product remaining in the corundum crucible is a mixture of PET residue, KOH, and NaOH. These mixtures are dissolved, filtered, rinsed, dried, and weighed, and the mass of PET remaining after the reaction can be calculated.
[0045] The schematic diagram of the device for degrading polyethylene terephthalate used in all embodiments of the present invention is as follows: Fig.13 As shown. A stainless steel reactor can be used as the reaction container 3, a corundum crucible is placed inside, and the reactor is sealed with a high temperature resistant sealant to prevent gas leakage during the reaction process. High temperature resistant cotton is placed on the reactor to play a role in heat preservation. The power supply 1 can use a DC regulated power supply to provide a certain external voltage, and the working voltage range is (0V to 30V).
[0046] The electric heating furnace 2 is used for heating the reaction kettle, and has an operating temperature range of (0°C to 700°C). One end of the electric heating furnace is connected to a transformer, and the heating rate of the electric heating furnace is controlled by the transformer.
[0047] The function of the temperature control box 10 is to stabilize the temperature within a certain range. It measures the temperature of the reaction center through a K-type thermocouple 4, and the temperature control range is -50°C to 1000°C.
[0048] The function of the pump 8 (for example, a low-flow air pump) is to discharge the gas generated by the reaction from the reactor under the action of the pressure difference. The output flow rate of the gas can be controlled by adjusting the pressure difference.
[0049] The function of the U-shaped tube 6 is to condense the high boiling point components generated during the reaction on the inner wall of the U-shaped tube 6. The U-shaped tube 6 is cooled in a water bath, and the condensation time of the high boiling point components in the U-shaped tube 6 is controlled by the valve above it.
[0050] The function of the drying tube 7 is to allow the gas generated after the reaction to pass through the color-changing silica gel to absorb the water vapor therein.
[0051] A gas bag 9 may be included to collect the resulting gas.
[0052] A digital multimeter can be used, which measures the current or voltage in a circuit by connecting it in series or in parallel. One end of the multimeter can be connected to a computer to measure the trend of current or voltage over time. It can also check whether the motor is connected to cause a short circuit by measuring resistance.
[0053] Example
[0054] Reagents, instruments and equipment
[0055] The main chemical reagents, instruments and equipment used in the examples are shown in Tables 1 and 2 below.
[0056] Table 1. Main chemical reagents used in the experiments.
[0057] Reagent name Grade / Model Manufacturer Polyethylene terephthalate DuPont 545 DuPont Potassium hydroxide Analytical grade Tianjin Damao Chemical Reagent Factory Sodium hydroxide Analytical grade Tianjin Damao Chemical Reagent Factory Distilled water - self made Sodium chloride Analytical grade Tianjin Damao Chemical Reagent Factory Acetonitrile Analytical grade Lianlong Bohua (Tianjin) Pharmaceutical Chemical Co., Ltd. Carbon tetrachloride Analytical grade Lianlong Bohua (Tianjin) Pharmaceutical Chemical Co., Ltd. Color changing silicone - Qingdao Guichuang Distillation Chemical Co., Ltd.
[0058] Table 2. Experimental instruments used in the examples.
[0059]
[0060] The device used in the embodiment is as follows Fig.13 As shown, the alkali mixture of KOH and NaOH plays a vital role in obtaining a low-temperature molten salt supporting electrolyte. In this case, KOH and NaOH electrolytes are used to provide hydrogen and oxygen elements with high conductivity and low melting points. The commercial electrical instruments used are a constant potential instrument and an electric heater. Both the anode and cathode are fixed in an alumina crucible, maintaining a space of 1 cm. The reactor is installed with a graphite packing as a gasket and then sealed with bolts and nuts. The condenser, drying tube and collecting tube are connected to the reactor respectively. The reactor in the heating furnace is heated to the required temperature at a rate of 9℃-10℃ / min. In the ongoing reaction, the gaseous products are absorbed and washed by the condensing device (water-cooled U-shaped tube) and the drying device (drying tube filled with color-changing silica gel). The liquid products are collected in the U-shaped tube. The surrounding gas is pressed into a gas collection bag for subsequent analysis. The liquid phase and the solid phase are separated by the method described in the product analysis section.
[0061] How to operate
[0062] (1) Preparation of spiral electrode: A spiral electrode with a diameter of 1 cm was made by winding a nickel wire with a diameter of 0.8 mm. The number of windings was 10, the total length of the nickel wire was 26 cm, and the surface area S ≈ 6.53 cm 2 .
[0063] (2) Preparation of PET / KOH / NaOH mixed system: Dry PET at 100°C in an oven for 5 minutes. Weigh 2.8g KOH, 0.5g PET particles, and 2.0g NaOH. Place them in a pre-dried corundum crucible (diameter × height = 40mm × 80mm) and mix them evenly.
[0064] (3) Seal the reaction system and heat it: insert two electrodes into the corundum crucible, and keep a distance of 1 cm between the two electrodes. Use high-temperature resistant sealant to seal the reactor and fasten the reactor with bolts and nuts. Connect the condensing device, drying device, and gas collection device respectively. Put the reactor into the heating furnace, turn on the power of the temperature control box, adjust the heating rate to 9℃~10℃ / min, and raise the temperature of the reactor to the preset temperature (the preset temperatures are set to 400℃, 410℃, 420℃, 430℃, and 440℃ respectively).
[0065] (4) Apply voltage or current to the reaction system: When the temperature of the reactor is stabilized at the preset temperature, adjust the DC regulated power supply to provide a preset voltage (1.5V) or a preset current (100mA, 200mA, 300mA, 400mA, etc.), so that the reaction system reacts at the pre-set temperature and voltage.
[0066] (5) Collection of gaseous products: After the reaction lasts for a predetermined time, turn off the electric heating furnace and the DC regulated power supply. Turn on the low-flow air sampling pump to squeeze the argon gas in the air bag on the left into the reactor. The gas is sampled once every minute for 15 seconds each time, and 10 times are sampled. The valve of the condensation device is closed during the gas sampling interval to fully condense the gaseous products. After the product is collected, the reactor is first cooled in a sand bath, and then cooled in a water bath when the temperature drops to about 200°C.
[0067] (6) Collection of solid products: After the reaction has been carried out for a predetermined time, PET has not been completely degraded, so the residual substances after the reaction need to be processed to facilitate the calculation of the conversion rate of PET. After condensation, part of the gas phase organic matter is converted into liquid, and the other part is collected in the form of gas. Therefore, what remains inside the corundum crucible is a mixture of PET residue, KOH, and NaOH. These mixtures are dissolved, filtered, rinsed, dried, and then weighed to calculate the mass of PET remaining after the reaction.
[0068] Product analysis method
[0069] Gas phase product analysis method
[0070] (1) Three-phase separation and quantitative method
[0071] By the above method, PET is depolymerized to obtain three products: gas phase, liquid phase and solid phase. The high-temperature gas phase is condensed into gas and liquid organic molecules after passing through the condenser, and the air sampling pump is used to collect the gas for detection. The liquid product condensed on the inner wall of the U-tube is collected, and the aqueous solution is extracted with ether to obtain water and organic phase, the organic solvent part is removed, and the extracted aqueous phase is distilled by distillation and concentration method to separate the water-soluble organic matter in the aqueous phase to obtain a liquid phase product. Finally, the solid phase product is a compound insoluble in water and organic solvents, consisting of unreacted PET, carbon and high carbon polymers. After the reaction is carried out for a period of time, PET does not achieve complete degradation, so it is necessary to process the residual substances after the reaction to facilitate the calculation of the conversion rate of polypropylene. Therefore, what remains inside the corundum crucible is a mixture of polypropylene residue, KOH and NaOH. These mixtures are dissolved, filtered, rinsed, dried and weighed to calculate the mass of PET remaining after the reaction.
[0072] (2) Gas analysis method
[0073] In this experiment, the refinery gas analyzer GC-7890B produced by Agilent was used to perform qualitative and quantitative analysis on gas phase products. The gas chromatograph is equipped with five valves, seven chromatographic columns, two TCD detectors, and one FID detector. The FID channel is configured with a PONA capillary column, and the carrier gas is He gas, which can detect hydrocarbons from C1 to C5. The first TCD channel, with helium as the carrier gas, can monitor fixed gases, including CO2, CO, O2, and N2; the second TCD detector, with N2 as the carrier gas, can analyze hydrogen components. This chromatographic system can detect most of the light hydrocarbons from C1 to C5, and the volume fraction of each component can be determined based on the working curve.
[0074] Solid analysis methods
[0075] (1) XRD analysis and field emission scanning electron microscopy analysis
[0076] Scanning electron microscopy is used to observe the porosity of the solid product; field emission scanning electron microscopy is used to display the microscopic crystal structure of the solid product and observe the microporosity of the solid product, thereby observing and describing the relationship between microstructure and porosity through field emission scanning electron microscopy. In the embodiment, the application value of the product is judged by the composition and morphology of the solid product after the reaction, and the solid product is detected by field emission scanning electron microscopy (Zessiss SigmaHV) and XRD (D / max-2200X), and the composition of the solid product after the reaction is roughly judged and its porosity is observed.
[0077] Calculation of PET total conversion rate, liquefaction rate and gasification rate
[0078] By weighing the mass of the U-shaped condenser before and after the reaction, the mass W of the liquid product generated by the reaction can be calculated. L Then, according to the mass W' of the solid residue obtained in the post-reaction treatment process, the total conversion rate, liquid yield and gas yield of the degraded PET were calculated.
[0079] θ D(PET) =(W-W') / W×100% (5-1)
[0080] θ L(PET) =W L / W×100% (5-2)
[0081] θ G(PET) =θ D -θ L (5-3)
[0082] θ D(PET) ,θ L(PET) ,θ G(PET) They are the total conversion rate, liquid yield, and gas yield of degraded PET respectively;
[0083] W-PET mass before conversion;
[0084] W'-mass of solid residue after reaction;
[0085] W L - Liquid phase product quality.
[0086] Results and Discussion
[0087] Thermogravimetric curve analysis
[0088] exist Figure 1It can be seen that under air flow, the temperature range is 25℃ to 900℃, and the heating rate is 4℃ / min when the air flow rate is 100mL / min. It can be seen from the figure that when the temperature is less than 400℃, the mass of PET is basically unchanged, and the mass loss rate is almost zero, indicating that the PET molecular chain is almost not broken and oxidized at this time; between 400 and 525℃, the mass loss rate of PET increases with the increase of temperature, and at about 525℃, its mass loss rate reaches the maximum value, indicating that the degree of random chain breaking and oxidation of PET in this temperature range is becoming more and more intense; after 525℃, the mass loss rate is getting smaller and smaller, indicating that the degree of PET molecular chain breaking and oxidation is getting weaker and weaker at this time. There are three endothermic peaks in the DSC curve. The first endothermic peak at 254.1℃ is generated by the melting of PET, and the second peak observed at 466.8℃ is due to the decomposition of PET, accompanied by a decrease in mass.
[0089] Thermally Assisted Cyclic Voltammetry Analysis of PET
[0090] Figure 2 The thermally assisted cyclic voltammetry curves of PET at different temperatures (400°C and 420°C) are shown. The scanning rate is 30mV / s and the scanning range is -1.5V to 1.5V (relative to the counter electrode). Obvious oxidation peaks appear at 400°C and 420°C, indicating that electrochemical oxidation reactions occur during the degradation of PET. Moreover, the oxidation potential of the oxidation peak at 420°C is lower than that of the oxidation peak at 400°C. The oxidation potential decreases with increasing temperature, indicating that increasing temperature is conducive to the electrochemical oxidation reaction during the degradation of PET. In addition, hydrogen ions in water undergo reduction reactions to generate hydrogen.
[0091] The dual field effect of heat energy and electric energy is a coupling effect. Under the action of the electric field, the pyrolysis temperature drops significantly; under the action of the thermal field, the electric field electrolysis potential drops. The cyclic voltammetry results show that the electrochemical oxidation reaction of PET can be promoted by regulating the input of heat energy and electricity during the reaction.
[0092] Effect of current intensity on PET degradation efficiency
[0093] At 400℃, the reaction time was 120min, and PET was oxidatively degraded at 0mA, 100mA, 200mA, 300mA, and 400mA respectively; the dosages of PET, KOH, and NaOH were 0.5g, 2.8g, and 2.0g respectively. The degradation effect of PET was analyzed by comparing the total conversion rate, gasification rate, and liquefaction rate of the reaction. By comparing with the thermal cracking method, the difference in degradation effect between the thermoelectric coupling reaction and the thermal cracking reaction was investigated.
[0094] Depend on Figure 3As shown in the figure, at 400℃, as the current increases, the total conversion rate of PET shows an upward trend. When the current is 400mA, its total conversion rate reaches 27.37%, while the total conversion rate during thermal cracking is only 8.32%, an increase of 19.05%. This shows that the thermoelectric coupling reaction can degrade PET more efficiently, and increasing the current is conducive to degradation.
[0095] In addition, as the current increases, the degradation gas conversion rate increases from 7.34% to 20.90%, which may be due to the thermoelectric coupling reaction promoting the decomposition of PET macromolecules into a series of small molecules.
[0096] Effect of temperature on PET degradation efficiency
[0097] The constant voltage was 1.5V, the reaction time was 120min, and PET was oxidatively degraded at 400℃, 410℃, 420℃, 430℃ and 440℃ respectively; the dosages of PET, KOH and NaOH were 0.5g, 2.8g and 2.0g respectively. By keeping other conditions such as voltage unchanged, the effect of temperature on PET degradation was investigated.
[0098] from Figure 4 It can be seen that when other conditions are the same, when the reaction temperature is 400℃~440℃, the total conversion rate of PET increases from 8.32% to 43.95%, an increase of 35.63%; the gas conversion rate increases from 7.34% to 26.17%, an increase of 18.83%; the liquid conversion rate increases from 0.98% to 17.78%, an increase of 16.80%, all of which increase with the increase of temperature.
[0099] from Figure 5 It can be seen that when other conditions are the same, when the reaction temperature is 400℃~440℃, the total conversion rate of PET increases from 11.32% to 65.49%, an increase of 54.17%; the gas conversion rate increases from 10.16% to 40.76%, an increase of 30.6%; the liquid conversion rate increases from 1.16% to 24.73%, an increase of 23.57%, all of which increase with the increase of temperature.
[0100] By comparing the experimental results of the electro-thermal degradation process with those of single pyrolysis, it was found that when the reaction temperature was 440°C, the total conversion rate of PET by electro-thermal degradation was 65.49%, which was 21.54% higher than that of single pyrolysis at 43.95%. This shows that the electro-thermal degradation process is beneficial to improving the conversion rate of PET degradation. The thermal-electric dual field effect is a coupling effect. The system simultaneously has thermal cracking reaction and electrochemical reaction of PET. Under the action of the electric field, the pyrolysis temperature drops significantly.
[0101] Effect of reaction time on PET degradation efficiency
[0102] In the examples, the relationship between the conversion rates of PET in single pyrolysis and thermoelectric coupled degradation and the time is investigated. The experimental conditions are as follows: the reaction temperature is 400°C, the PET dosage is 0.5g, the KOH and NaOH dosages are 2.8g and 2.0g, respectively. The indoor simulation experiment of PET degradation to fuel and hydrogen production was carried out for 60min, 120min, 180min, 240min, and 300min, respectively. The experimental results are as follows: Figure 6 shown.
[0103] from Figure 6 It can be seen that when other conditions are the same and the reaction time is 1h to 5h, the total conversion rate of PET increases from 3.23% to 39.12%, an increase of 35.89%; the gas conversion rate increases from 0.26% to 13.77%, an increase of 13.51%; the liquid conversion rate increases from 2.97% to 25.35%, an increase of 22.38%, all of which increase with the extension of the reaction time.
[0104] from Figure 7 It can be seen that when other conditions are the same and the reaction time is 1h to 5h, the total conversion rate of PET increases from 6.95% to 44.84%, an increase of 37.89%; the gasification rate increases from 6.36% to 16.69%, an increase of 21.79%; the liquefaction rate increases from 0.59% to 28.15%, an increase of 16.10%, all of which increase with the extension of the reaction time.
[0105] As time goes by, the total conversion rate and gasification rate of PET show an upward trend. Comparing the experimental results of thermoelectric coupling degradation and single pyrolysis, it is found that the total conversion rate of thermoelectric coupling degradation is 44.84% when the reaction time is 300min, which is 5.72% higher than the 39.12% of single pyrolysis. This may be due to the extension of time, which shows that the use of thermoelectric coupling degradation is beneficial to improve the conversion rate of PET plastic degradation. Under the dual coupling of thermal field and electric field, the system simultaneously has thermal cracking reaction and electrochemical reaction of PET, and the content of PET being degraded gradually increases. After the PET macromolecules are degraded into small molecules, they are separated from the electrode surface in the form of gas. Then, the main chain and side chain of PET "queue up" to react with the electrode to produce redox reaction.
[0106] Solid phase product analysis
[0107] According to the above reaction condition screening and optimization, under the conditions of 440°C, voltage 1.5V, and reaction time 120min, the total conversion rate of the thermoelectric coupled degradation of PET was 65.49%, which is 1.49 times that of single pyrolysis, and is the best condition optimized in the embodiment.
[0108] The inventors filtered and dried the solid product of thermoelectric coupling degradation of PET at 440°C, voltage 1.5V, reaction time 120min, and performed XRD and SEM analysis. The structure of the solid product and the morphology of the distributed solid particles were determined by field emission scanning electron microscopy (FESEM Zeiss Sigmal HV); the crystal structure was determined by X-ray diffraction (GIXRD Rigaku D / max-2200, copper target, scanning range 2θ=20-80°).
[0109] Further information can be obtained from the SEM morphology of samples such as Figure 8 ac: SEM micrographs of the solid product obtained at 440°C and 0V. Figure 8 b is characterized by the presence of large irregularly shaped particles with sharp edges and sizes up to several hundred micrometers. It can be seen that despite heating in air, there are no signs of oxidation on the material, indicating its high resistance to oxidation.
[0110] SEM micrograph of the solid product obtained at 440 °C, 1.5 V ( Fig. 9 a, b and c) show features that are roughly the same as those observed on the material obtained at 440°C. Unlike the SEM micrograph at 440°C and 0V, the material in the thermoelectric coupled electron micrograph shows a large number of pit-like morphologies, which is a sign of the initial stage of oxidation. This shows that the target chemical conversion rate of PET degradation can be greatly improved in the process of thermoelectric coupled degradation of PET to produce fuel and synergistic hydrogen production. The thermochemical cracking reaction and electrochemical oxidation reaction of PET degradation are promoted through the thermal-electric dual field coupling effect. Even more surprising is that the solid product residue obtained after the reaction undergoes obvious carbonization.
[0111] Fig.10 and Fig.11 The XRD analysis of the samples obtained from the X-ray diffraction curves of the solid products of thermoelectric coupling and single pyrolysis at 440°C respectively shows the presence of a (002) peak of hexagonal graphite at 2θ=25.9°. The broad peak with a maximum value of 2θ=42.5° corresponds to overlapping (100) and (101) reflections, so that the PET degradation product at 440°C generates amorphous carbon instead of obtaining useless secondary waste as in the prior art. Therefore, the method of the present invention is a green, environmentally friendly, efficient and low-cost technical solution for converting solid residues after the degradation of waste PET bottles into activated carbon with economic value.
[0112] Gas phase product analysis
[0113] Depend on Fig.12As shown in the figure, the gas products of PET degradation under the conditions of 440℃ and 2h reaction are compared. Through thermoelectric coupling degradation of PET, the hydrogen yield can be 33mL, which is 8.99 times the hydrogen yield of single thermal degradation; the methane content after thermoelectric coupling degradation is 31.4mL, which is 10.5 times that of single pyrolysis. This shows that in the process of thermoelectric coupling degradation of PET, the coupling of heat and electricity changes the chemical reaction pathway. The use of electric-thermal fields to synergistically drive the two chemical processes of PET thermochemical and electrochemical degradation can improve the conversion rate of the PET degradation process and obtain higher yields of light hydrocarbon fuels and hydrogen.
[0114] It can be seen from the above results that the degradation of PET by thermal-electrochemical coupling can greatly promote the efficient and highly selective production of hydrogen and light hydrocarbon fuels; in the above experimental design, the reaction temperature is 440°C, the constant voltage is 1.5V, the PET dosage is 0.5g, the sodium hydroxide is 2.0g, the potassium hydroxide is 2.8g, and the reaction time is 120min. The total conversion rate of PET reaches 65.49%, which is 1.49 times that of single pyrolysis; by gas chromatography analysis of the PET degradation gas phase products, under the conditions of 440°C, voltage 1.5V, and reaction time of 120min, the thermoelectric coupled cracking gas has obtained a gas product with high added value. , among which the volume of hydrogen is 8.99 times that of single pyrolysis; the volume of methane is 31.4mL, which is 10.5 times that of single pyrolysis; after XRD and SEM analysis of the solid products of PET degradation, it was found that amorphous carbon can be generated in the solid products of PET degradation. Compared with the solid products generated by single pyrolysis, there are irregular particles with sharp edges and a size of up to several hundred microns, while the SEM images of thermoelectric coupled degradation show a large number of pit-like morphologies, indicating that thermoelectric coupled degradation significantly improves the conversion rate of PET degradation and obtains more valuable solid products, making PET degradation achieve almost 100% recycling.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for degrading polyethylene terephthalate, characterized in that: The method comprises the following steps: (1) Put potassium hydroxide, polyethylene terephthalate and sodium hydroxide into a crucible and mix them evenly; (2) inserting two electrodes, serving as a cathode and an anode, into a crucible, fixing the crucible in a reactor, sealing the reactor and heating it, and after the temperature of the reactor stabilizes at a first preset temperature, applying a preset voltage and a preset current to the reactor for degradation, and collecting gaseous products and liquid products, wherein the preset voltage is 1.4 to 1.6 V, the preset current is 0.1 A to 0.4 A, and the degradation time is 60 min to 300 min; (3) lowering the temperature of the reactor to a second preset temperature, and then cooling it to room temperature; (4) Collecting the solid phase product in the reactor; Wherein, the mass ratio of potassium hydroxide, polyethylene terephthalate and sodium hydroxide is (4-6):1:(3-5); the first preset temperature is 400°C to 440°C, and the second preset temperature is 150°C to 250°C.
2. The method according to claim 1, characterized in that: In step (2), the electrode is a spiral electrode.
3. The method according to claim 2, characterized in that: The spiral electrode is made by winding nickel wire.
4. The method according to claim 2, characterized in that: The diameter of the spiral electrode is 1.8 cm to 1.2 cm.
5. The method according to claim 3, characterized in that: The diameter d of the nickel wire is 0.5 mm to 1 mm, the total winding length l of the nickel wire is 20 cm to 30 cm, and the number of windings is 10 to 20.
6. The method according to any one of claims 1 to 5, characterized in that: In step (1), the polyethylene terephthalate is dried at 90 to 110° C. for 4 to 6 minutes before being placed in the crucible.
7. The method according to claim 6, characterized in that: The crucible is a corundum crucible.
8. The method according to claim 6, characterized in that: The size of the crucible is diameter×height=40 mm×80 mm.
9. The method according to claim 6, characterized in that: The crucible was pre-dried before use.
10. The method according to any one of claims 1 to 5, characterized in that: In step (2), the distance between the two electrodes is 0.8 cm to 1.2 cm.
11. The method according to any one of claims 1 to 5, characterized in that: In step (2), the heating rate is 9°C to 10°C / min.
12. The method according to any one of claims 1 to 5, characterized in that: In step (2), the first preset temperature is 440° C., the preset voltage is 1.5 V, and the degradation time is 120 min.
13. The method according to claim 11, characterized in that: In step (2), the preset current is 0.4A.
14. The method according to any one of claims 1 to 5, characterized in that: In step (3), the gaseous products are collected in the following manner: argon gas is introduced into the reactor, and the gaseous products in the reactor are collected into a gas bag by using the Ar exhaust method.
15. The method according to any one of claims 1 to 5, characterized in that: In step (4), the solid phase product is obtained in the following manner: after the degradation is completed, the solid phase product in the reactor is dissolved in water, neutralized with hydrochloric acid to pH = 2.5 to 3.5 to obtain a solid suspension, filtered, and the obtained solid is washed with acetone and then dried.
Citation Information
Patent Citations
Method for degrading polypropylene to efficiently produce hydrogen and light dydrocarbon through solar heat-electrical coupling
CN108588738A
Method for degrading plastic material waste by pyrolysis for transformation into hydrocarbon mixture to be used as fuel
WO2001018152A1